STYLES CERAMIQUES DE TOUMODI (ZONE DES BAS-GLACIS DE COTE D’IVOIRE) : CONTRIBUTION A LA CONNAISSANCE DES DEBUTS DU NEOLITHIQUE A L’AGE DU FER EN AFRIQUE DE L’OUEST3 - Siméon, Kouassi Kouakou; Hélène, Kienon-Kabore Timpoko (European Scientific Journal, ESJ, 2012)
The debuts of the Neolithic as well as the passage of the latter at the beginning of the Iron Age in Ivory Coast (3 000 av. J-C and 500 ap. J-C generally) in zone of forest as in zone of savanna, are characterized by relatively numerous sites. Mauny, R. 1972 and Chenorkian, R. On 1983 indicate (appoint, sometimes indicate, sometimes appoint) them of Mesonéolithique or Neolithic; so indicating that the transition between the Mesolithic and the Neolithic is much less clear in forest than in savanna. The region of Toumodi, in this context, appears as one of the centers the richest in the country (Mauny, R. 1972). The prospecting made in the region in March, 2010 by the teaching staff of the department of Archaeology of the Institute of the Anthropological Sciences of Development (ISAD) - University of Cocody-Abidjan, opens new perspectives on the debuts of the Neolithic to the Iron Age in Ivory Coast, through the numerous fragments of ceramic associated sometimes to cut axes, polished axes and brought to light polishers. From a morphological study and from the internal and external analysis the aforementioned ceramic, we show the ceramic styles of the region and we make suggestions as for an adequate study of the Neolithic for the Iron Age in Côte d’Ivoire.